Застосування ігрової моделі для дослідження оптимальності систем захисту інформанті - Румянцева, О. В. (ХНУРЕ, 2023)
The report reviews the application of a game model to investigate the optimality of information security systems. The report also highlights the importance of considering multiple stakeholders and their competing interests when designing a secure system. It outlines the steps involved in developing a game model, including identifying players, defining strategies. The report described how simulation and optimization techniques can be used to evaluate different scenarios and identify the optimal solution. Ultimately, the report concludes that game models can provide a useful tool for designing secure systems and highlights its potential to improve decision-making in the field of information security.